1986
DOI: 10.1002/app.1986.070320107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chalk and its surface treatment on crystallization of filled polypropylene

Abstract: SynopsisIsotactic polypropylene has been shown to crystallize from the melt spherulitically at intermediate undercoolings (100 -130°C) in the presence of a high amount (40 wt %) of chalk (calcium carbonate). Linear growth rate is not remarkably affected by the presence of a filler. Both nonisothermal and isothermal crystallization DSC experiments indicate that chalk acts as a weak nucleant. Introduction of liquid [oligomer of ethylene oxide (OEO), M , = 3001 at polymer-filler interface lowers the nucleating ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…However, it is generally assumed that non-integral values of n are caused by factors such as secondary crystallization and mixed nucleation modes, rather than being a genuine reflection of non-three dimensional development. Under these circumstances, Kowalewski and Galeski (32) suggested that the effective 3-dimensional crystallization rate constant, K 3 , can be determined from the experimentally measured K exp using the relationship: -( ) (2) where N represents the number of nucleation sites per unit volume and G is the growth rate of the crystallizing objects. The value of this approach is that heterogeneous nucleation is closely related to the local interactions that occur between the crystallizing polymer and the substrate -the difference energy parameter in the theory of Muchová and Lednický (35) .…”
Section: Crystallization Behaviourmentioning
confidence: 99%
“…However, it is generally assumed that non-integral values of n are caused by factors such as secondary crystallization and mixed nucleation modes, rather than being a genuine reflection of non-three dimensional development. Under these circumstances, Kowalewski and Galeski (32) suggested that the effective 3-dimensional crystallization rate constant, K 3 , can be determined from the experimentally measured K exp using the relationship: -( ) (2) where N represents the number of nucleation sites per unit volume and G is the growth rate of the crystallizing objects. The value of this approach is that heterogeneous nucleation is closely related to the local interactions that occur between the crystallizing polymer and the substrate -the difference energy parameter in the theory of Muchová and Lednický (35) .…”
Section: Crystallization Behaviourmentioning
confidence: 99%
“…Assuming that the nucleation occurs instantaneously, and taking into account the dimensions of the spherulites are proportional to the C3-content in EPR. approximation of Kowalewski and Galeski, 22 the density of the crystallization nuclei, N, is given by the following equation:…”
Section: Introductionmentioning
confidence: 99%
“…A similar finding was reported earlier: CaCO 3 acted as a nucleating agent in the crystallization of PP, and this effect was more pronounced with untreated CaCO 3 than a stearic acid coated type. 25,26 The percentage of crystallinity observed in the filled composites is lower than that of unfilled PP, and this can be explained by the substitution of PP by the rigid filler. To compare the crystallinity of only the crystallizable component in each sample, the percentage of crystallinity per unit weight of the crystallizable component was calculated and reported as a percentage of the normalized crystallinity.…”
Section: Resultsmentioning
confidence: 92%